Conservation Partnership in the Management of Tesso Nilo National ParkRiau Province, Indonesia - Lestari, Ister; Hidir, Achmad; Marnelly, T. Romi (Journal of Authentic Research, 2026)
Tesso Nilo National Park, located in Southeast Asia, is home to 3% of the world's mammal species, including endangered species such as the Sumatran elephant and Sumatran tiger, and possesses high biodiversity. However, over the past two decades, its forest cover has faced significant threats, primarily due to population growth and the expansion of oil palm plantations. This study aims to analyze the conservation partnership program implemented by the Tesso Nilo National Park Office to restore forest functions and promote sustainable forest management. The research uses a qualitative case study approach. Findings reveal that the Tesso Nilo National Park Office regularly engages with surrounding communities. Through the Job Creation Law (Undang-Undang Cipta Kerja), the community has been introduced to mechanisms for managing conservation areas and the implementation of ecosystem restoration partnerships. Eligible communities have agreed to collaborate with the park's office to rehabilitate degraded areas with multifunctional forest crops, including jengkol (Archidendron pauciflorum), durian, mangosteen, candlenut, avocado, and others, using the heteroculture planting method. This study concludes that effective conservation partnerships require active collaboration from all parties, supported by clear policies, especially from the Ministry of Forestry.